The relationship between Individual Entrepreneurial Orientation (IEO) and entrepreneurial intention - Wei-Loon Koe (Journal of Global Entrepreneurship Research, 2016)
The importance of entrepreneurship to a nation development is unneglectable. Malaysian government has carried out various supporting activities to promote entrepreneurial activities in the country. However, the results were less embracing, especially among the young adults. As such, understanding of what influence young adults' intention towards entrepreneurship is important in the effort of entrepreneurship development. This study was carried out to address the university students' level of entrepreneurial intention and the influence of individual entrepreneurial orientation (IEO) on entrepreneurial intention. A questionnaire survey was conducted on 176 undergraduate students from a public university with 'entrepreneurial university' status. The results indicated that university students demonstrated intention towards entrepreneurship and were quite positive towards becoming entrepreneurs. In addition, university students' entrepreneurial intention was found to be positively affected by their quality of proactiveness and innovativeness. However, risk-taking ability was not an influential factor on entrepreneurial intention. Theoretically, this paper confirmed the importance of studying EO at the individual level. Practically, it suggested that higher learning institutions should pay careful attention in designing their entrepreneurship education curriculum. Specifically, the entrepreneurship training should focus on enhancing students IEO ability and increasing their entrepreneurial intention. Recommendations for future researchers have also been put forth at the end of this paper.
Keywords: 650; Entrepreneurial orientation; Entrepreneurial intention; Students; University